Technical education as a service to agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The technical education that is currently being provided in Africa today is often poorly adapted to local needs and conditions. Too many diploma holders find themselves among the unemployed. There are some interesting initiatives coming to light in...